Women farmers’ empowerment in south-eastern serbia: a case study - Ilić Krstić, Ivana; Miltojević, Vesna (Sociološki pregled, 2023)
Women’s empowerment in agriculture is discussed on the basis of two indicators: control over production resources and decision-making about agricultural production. The aim of this study is to determine the degree of empowerment of women farmers in South-eastern Serbia. The initial assumption is that the degree of empowerment of women farmers in this part of Serbia is low. The empirical study, conducted using a specially designed questionnaire, encompassed 132 women farmers in the Municipality of Svrljig. The results indicate a low degree of empowerment among women who participate in agricultural production, because a low percentage of the women own agricultural resources and make independent decisions about agricultural production. Such results are significant, as they emphasise the need for further examination of the degree of empowerment and calculation of women farmers’ empowerment index, as well as the need for taking specific measures at the local, regional, and national levels.